Misdiagnosis of asthma in schoolchildren. Issue 3 (9th August 2016) - Yang, C.L.; Simons, E.; Foty, R.G.; Subbarao, P.; To, T.; Dell, S.D.
Summary: Background: A correct diagnosis of asthma is the cornerstone of asthma management. Few pediatric studies have examined the accuracy of physician‐diagnosed asthma. Objectives: We determined the accuracy of parent reported physician‐diagnosed asthma in children sampled from a community cohort. Methods: Nested case‐control study that recruited 203 children, aged 9–12, from a community‐based sample. Three groups were recruited: asthma cases had a parental report of physician‐diagnosed asthma, symptomatic controls had respiratory symptoms without a diagnosis of asthma, and asymptomatic controls had no respiratory symptoms. All participants were assessed and assigned a clinical diagnosis by one of three study physicians, and then completed spirometry, methacholine challenge, and allergy skin testing. The reference standard of asthma required a study physician's clinical diagnosis of asthma and either reversible bronchoconstriction or a positive methacholine challenge. Diagnostic accuracy, sensitivity and specificity were calculated for parent‐reported asthma diagnosis compared to the reference standard. Results: One hundred two asthma cases, 52 controls with respiratory symptoms but no asthma diagnosis, and 49 asymptomatic controls were assessed. Physician agreement for the diagnosis of asthma was moderate (kappa 0.46–0.81). Compared to the reference standard, 45% of asthma cases were overdiagnosed and 10% of symptomatic controls were underdiagnosed. Parental report of physician‐diagnosed asthma had 75% sensitivity and 92% specificity for correctly identifying asthma. Conclusions: There is significant misclassification of childhood asthma when the diagnosis relies solely on a clinical history. This study highlights the importance of objective testing to confirm the diagnosis of asthma.Pediatr Pulmonol. 2017;52:293–302. © 2016 Wiley Periodicals, Inc.